Corrosion characteristics of copper and leaded bronze in palm biodiesel - Haseeb, A.S. Md. Abdul; Masjuki, Haji Hassan; Ann, L.J.; Fazal, M.A. (2010)
Biodiesel has become more attractive as alternative fuel for automobiles because of its environmental benefits and the fact that it is made from renewable sources. However, corrosion of metals in biodiesel is one of the concerns related to biodiesel compatibility issues. This study aims to characterize the corrosion behavior of commercial pure copper and leaded bronze commonly encountered in the automotive fuel system in diesel engine. Static immersion tests in B0, B50 and B100 fuels were carried out at room temperature for 2640 h. Similar immersion tests in B0, B100 and B100 (oxidized) fuels were also conducted at 60 degrees C for 840 h. At the end of the test, corrosion behavior was investigated by weight loss measurements and changes in surface morphology. Fuels were analyzed by using TAN analyzer, FTIR, MOA (multi-element oil analyzer) to investigate acid concentration, oxidation level with water content and corrosive impurities respectively. Results showed that under the experimental conditions, pure copper was more susceptible to corrosion in biodiesel as compared to leaded bronze. (C) 2009 Elsevier B.V. All rights reserved.